Enabling Self-passivation by Attaching Small Grains on Surfaces of Large Grains toward High-Performance Perovskite LEDs - Jiajun Qin; Jia Zhang; Yujie Bai; Shengbo Ma; Miaosheng Wang; Hengxing Xu; Matthew Loyd; Yiqiang Zhan; Xiaoyuan Hou; Bin Hu (iScience, 2019)
Summary: This paper reports a new method to generate stable and high-brightness electroluminescence (EL) by subsequently growing large/small grains at micro/nano scales with the configuration of attaching small grains on the surfaces of large grains in perovskite (MAPbBr3) films by mixing two precursor solutions (PbBr2 + MABr and Pb(Ac)2·3H2O + MABr). Consequently, the small and large grains serve, respectively, as passivation agents and light-emitting centers, enabling self-passivation on the defects located on the surfaces of light-emitting large grains. Furthermore, the light-emitting states become linearly polarized with maximal polarization of 30.8%, demonstrating a very stable light emission (49,119 cd/m2 with EQE = 11.31%) and a lower turn-on bias (1.9 V) than the bandgap (2.25V) in the perovskite LEDs (ITO/PEDOT:PSS/MAPbBr3/TPBi[50 nm]/LiF[0.7 nm]/Ag). Therefore, mixing large/small grains with the configuration of attaching small grains on the surfaces of large grains by mixing two precursor solutions presents a new strategy to develop high-performance perovskite LEDs. : Materials Characterization; Optical Materials; Surface Subject Areas: Materials Characterization, Optical Materials, Surface